Communication With Physicians as a Mediator in the Relationship Between the Nursing Work Environment and Select Nurse Outcomes in Jordan. Issue 6 (24th July 2018) - Al‐Hamdan, Zaid; Banerjee, Tanima; Manojlovich, Milisa
Abstract: Purpose: To test whether communication mediated relationships among nurses' work environments and nurse outcomes of job satisfaction and intent to stay. Design: This study used a cross‐sectional, quantitative survey design to query 650 nurses who worked in three hospitals in Jordan. Methods: We used Arabic versions of valid, reliable instruments measuring the nursing work environment, nurse perceptions of communication with physicians, intent to stay, and job satisfaction. Mediation analysis was used to test hypotheses. Findings: A total of 582 questionnaires were returned (89.5% response rate). Nurse perceptions of communication with physicians mediated the relationship between the nursing work environment and job satisfaction in medical, surgical, and critical care units. Nurse perceptions of communication with physicians mediated the relationship between the nursing work environment and intent to stay in all but maternity and "other" units. Conclusions: Depending on the nurse outcome, communication was a significant mediator for various unit types. These results may be related to the type of work that is done in each unit and the influence of patient care. Communication is one of many mechanisms that can specify how a positive nursing work environment can contribute to nurses' job satisfaction and intent to stay. Clinical Relevance: A potential solution to the nursing shortage in Jordan emerges by identifying communication with physicians as a mediator in the relationship between the work environment and selected nurse outcomes.